2019
DOI: 10.1128/jcm.01555-18
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Mycoplasma genitalium Antimicrobial Resistance Differ by Both Region and Gender in the State of Queensland, Australia: Implications for Treatment Guidelines

Abstract: Mycoplasma genitaliumis frequently associated with urogenital and rectal infections, with the number of cases of macrolide-resistant and quinolone-resistantM. genitaliuminfection continuing to increase. In this study, we examined the levels of resistance to these two common antibiotic treatments in geographically distinct locations in Queensland, Australia. Samples were screened for macrolide resistance-associated mutations using a commercially available kit (ResistancePlus MG; SpeeDx), and quinolone resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 32 publications
2
34
0
1
Order By: Relevance
“…NC_000908.2) was used as a reference strain. Amino acid changes in the QRDRs of the gyrA and parC genes in this study were compared with previous studies [6,24,26,33,38,41].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…NC_000908.2) was used as a reference strain. Amino acid changes in the QRDRs of the gyrA and parC genes in this study were compared with previous studies [6,24,26,33,38,41].…”
Section: Discussionmentioning
confidence: 94%
“…The uoroquinolone moxi oxacin, another medication extensively used as a second-line bactericidal, has a cure rate approaching 100% in infections with susceptible strains [36]. In recent years, the e cacy of moxi oxacin failure rate has also been noted, rst in Japan [7] and later in Australia [37][38][39]. The elimination rate of moxi oxacin for M. genitalium infection has decreased from 100% to 89% since 2010 [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, few studies have assessed the role of these different scenarios in treatment failure. Investigating the molecular epidemiology of M. genitalium may shed light on these events and improve control of this infection [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Although the populations have differed among studies, similarly high rates of macrolide resistance (Table 4). 3,[23][24][25][26][27][28] Several studies also demonstrated consistent increases in resistance rates over time. 3,28,29 All mutations detected in this study have been described previously; while C184T (Pro62Ser) in parC is of unknown significance, others are known to confer antibiotic resistance leading to higher minimal inhibitory concentrations and treatment failure.…”
Section: Discussionmentioning
confidence: 79%